All-suture anchors in arthroscopic acetabular labral repair: our experience - Di Benedetto, Paolo; Giovanni, Gorasso; Luigi, Castriotta; Francesco, Mancuso; Piero, Giardini; Causero, Araldo (Acta Biomedica Atenei Parmensis, 2020)
Background: Over the past years, the role of the acetabular labrum in hip joint biomechanics and its relations with joint health has been of particular interest. There is a good clinical improvement of patients in whom the acetabular labrum is preserved during arthroscopic hip surgery. The purpose of this study is to report the results of arthroscopic repair of labral tears at a medium term follow up. Materials and methods: We performed a retrospective review of all cases that underwent hip arthroscopy at our Institution from January 2013 until December 2018. There were 24 patients, 13 males and 11 females, and their mean age at the time of surgery was 29, 42 years (range, 19 to 43 years). All patients were treated by the same surgeon with an extracapsular OUT-IN approach. Suture was performed using a non-absorbable suture anchor all-suture. Clinical assessment was performed at December 2019 using a modified Harris hip score (mHHS), hip outcomes score activities of daily living (HOS ADL), hip outcomes score activities of sport scale (HOS SS). All patients with acetabular labrum injury had femoro-acetabular impingement. Results: The mean overall values in the preoperative period were 67.21 ± 10.31 for mHHS, 70.04 ± 12.11 for HOS-ADL and 60.06 ± 14.58 for HOS –SS. The results obtained in the re-evaluations of patients in December 2019 with a mean follow-up of 38, 3 months (minimum 1 year) are on average 82.17 ± 11.36 for mHHS, 83.00 ± 12.80 for HOS-ADL and 76.09 ± 18.52 for HOS-SS. Conclusions: The progress of knowledge and the advancement of diagnostic and therapeutic skills has led to a greater awareness of the importance of treating acetabular labrum tears. Arthroscopic treatment with suture appear to be a good option for these patients and we had encouraging results in our center.